Urinary Excretion of MicroRNA-126 Is a Biomarker for Hemangioma Proliferation. Issue 6 (June 2017) - Biswas, Ayan; Pan, Xueliang; Meyer, Melissa; Khanna, Savita; Roy, Sashwati; Pearson, Gregory; Kirschner, Richard; Witman, Patricia; Faith, Esteban Fernandez; Sen, Chandan K.; Gordillo, Gayle M.
Abstract : Background: Hemangiomas are unique endothelial cell tumors that involute spontaneously, which makes interpreting their response to therapies difficult. The objective of this work was to identify a potential biomarker in the urine of children with infantile hemangiomas that would facilitate testing new therapies. Methods: A prospective longitudinal study in children with hemangiomas and age-matched healthy controls was performed to determine whether microRNA-126, which is highly abundant in fetal endothelial cells, was more abundant in the urine of affected children. Prospective ultrasound measurements of hemangioma size and blood flow velocity were obtained as secondary endpoints to document longitudinal changes in untreated hemangiomas. Results: Urinary microRNA-126 levels were significantly elevated in children with proliferating hemangiomas, and relative levels of urinary microRNA abundance correlated with hemangioma size. Hemangiomas had elevated levels of microRNA abundance compared with healthy controls. Ultrasound data revealed that hemangioma proliferation typically stopped between 6 and 9 months of age. When hemangioma proliferation stopped, urinary microRNA-126 levels in children with hemangiomas dropped to levels observed in healthy age-matched controls. Conclusions: These are the first reported results to identify a potential microRNA biomarker in the urine of children with hemangiomas. Measurement of urinary levels of microRNA-126 could potentially be used to monitor hemangioma response to therapies. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, II.